Analysis of handover performance in mobile WiMAX network / Nurulhuda Abd Manan - Abd Manan, Nurulhuda (2013)
Mobile WiMAX is a fast growing broadband access technology that enables low-cost mobile Internet application. Data, voice and video streaming are the main application ofthe mobile WiMAX and the demand from the user is growing every day. The handover performance in mobile network is the most important factor that can influence the Quality of Service (QoS). The parameters such as throughput and packet delay are the main factors which affect the WiMAX network performance. This paper study the handover performance in term of handover delay, throughput and packet delay for three different traffic applications which are Voice over IP (VoIP), video conferencing and web browsing (HTTP). A different traffic give different handover delay time, throughput and packet delay during handover process.